Biodefence advanced materials and methods for health protection - Mikhalovsky, Sergey; Khajibaev, A. (NATO science for peace and security series A: chemistry and biology, 2011)
This book focuses on defence against biological warfare with an emphasis on applications of modern technologies and advanced materials in detection, health protection and medical treatment of the population. Specific topics include high-throughput sensitive detection methods, advanced nanostructured materials and techniques for external and internal protection of human health, as well as extracorporeal methods, adsorptive materials and bacteriophages decontaminating the human organism, and neutralising incorporated CBRN agents. The contributions describe recent developments in the field of biodefence aimed at protecting population against terrorism and terror related events. Broader approaches to reducing the impact of environmental pollution on human health and improving efficiency of medical treatment of patients with viral infections, poisoning and organ failure are also discussed.